2022
DOI: 10.3389/fped.2022.946579
|View full text |Cite
|
Sign up to set email alerts
|

The clinical application of flexible bronchoscopy in a neonatal intensive care unit

Abstract: ObjectiveFlexible bronchoscopy is widely used in infants and it plays a crucial role. The aim of this study was to investigate the value and clinical safety of flexible bronchoscopy in a neonatal intensive care unit.MethodsA retrospective analysis was performed on the clinical data of 116 neonates who underwent flexible bronchoscopy and the outcomes of 147 procedures. A correlation analysis was performed on the relationship between flexible bronchoscopy findings, microscopic indications, and clinical disease.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This rate was even higher in patients with suspected airway disease and ventilator-dependent patients (14). Ke reported that 147 neonates with FB showed at least one positive nding in 95.92% of patients (15). The high diagnostic contribution of FB was emphasized by the 87.5% detection rate of airway malformations or functional abnormalities in the 56 neonates in our study.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…This rate was even higher in patients with suspected airway disease and ventilator-dependent patients (14). Ke reported that 147 neonates with FB showed at least one positive nding in 95.92% of patients (15). The high diagnostic contribution of FB was emphasized by the 87.5% detection rate of airway malformations or functional abnormalities in the 56 neonates in our study.…”
Section: Discussionmentioning
confidence: 44%
“…Many studies have reported the safe use of bronchoscopy in neonates (15,21,27,30). In this study, the most common complications were hypoxemia (17.6%) and airway mucosal hemorrhage (14.3%).…”
Section: Discussionmentioning
confidence: 73%